The ESG Paradox: Sustainability Scores and Carbon Costs - Ilyona Risty (AKUNTANSI 45, 2025)
This study investigates the paradoxical relationship between Environmental, Social, and Governance (ESG) performance and carbon cost (CC) in the Asia–Pacific energy sector. While ESG scores are widely considered indicators of sustainable practices, their actual effectiveness in reducing carbon-related financial liabilities particularly in high-emission industries remains unclear. Using a sample of publicly listed energy companies in Asia–Pacific, the study employs panel regression analysis to assess the impact of ESG scores on projected carbon cost. ESG performance and carbon cost data were obtained from the S&P Global database. The results reveal a significant and positive association between ESG scores and carbon cost, indicating that firms with higher ESG performance tend to face greater carbon cost liabilities in the future. This suggests that, within the energy sector, high ESG ratings do not necessarily correspond to lower carbon exposure; instead, they may reflect enhanced transparency and disclosure, which makes future carbon risks more visible and quantifiable.